Pengaruh Sosialisasi Perpajakan, Kualitas Pelayanan dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Batam - Novianti, Lia; Hermaya Ompusunggu (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Compliance with motor vehicle tax obligations is an attitude or action that demonstrates adherence to the law and tax obligations related to the ownership and use of motor vehicles. The purpose of this study is to determine whether Taxation Socialization, Service Quality, and Tax Sanctions simultaneously influence Compliance with Motor Vehicle Tax Obligations in Batam City. This research adopts a quantitative research method. The data source used in this study is primary data in the form of questionnaires distributed to taxpayers. The population consists of motor vehicle taxpayers registered at the Batam Centre Samsat Office, totaling 484,829. The sample size determined for this study is 416 respondents, calculated using the Slovin's formula. Data analysis in this study includes instrument testing comprising validity and reliability tests, classic assumption tests including normality test, multicollinearity test, heteroskedasticity test, multiple linear regression analysis, and hypothesis testing consisting of t-test, F-test, and determination coefficient (R2). The results of this study indicate that Taxation Socialization, Service Quality, and Tax Sanctions individually and simultaneously have a significant influence on Compliance with Motor Vehicle Tax Obligations in Batam City.